Design and optimization of electrical submersible pumps (ESP) using PROSPER software for a well E-52 (Sebha University Conference Proceedings, 2024)
The decline in reservoir energy over time requires the use of artificial lift methods to maintain economic production rates in oil wells. This paper presents a comprehensive study on designing and optimizing Electrical Submersible Pump (ESP) systems using PROSPER software for under-saturated oil reservoir with weak water influx, experience a decline in reservoir energy over time, negatively affecting the economic production rates of oil wells. To address this challenge, artificial lift methods such as Electrical Submersible Pumps (ESPs) are required. By collecting and analyzing reservoir and well data, performing sensitivity analyses, and selecting optimum parameters. This study aims to design and optimize ESP systems to enhance well productivity and maintain economic production rates. Statistical error analysis was conducted to evaluate the reliability and accuracy of the optimization results, providing a quantified margin of error. The results from well E-52 show iimproved Production Efficiency: Significant production rate increase after ESP optimization (593 STB/day). After complete selecting of best ESP model that improve production, the selected TYEP was based on required power is 28.35hp and this value lowest value compared with other models, also gives best pump and motor efficiency with 63% and 83% respectively. Operation oil rate expected about 1500 STB/day by increasing 593 STB/day.  Limited Scope: Focus on a single well (E-52); broader validation needed. Cost Considerations: Lack of detailed financial analysis of ESP implementation.